Evaluación de la cito y genotoxicidad de la decocción de Aloysia citrodora paláu mediante Allium test - Miraglia, C.; Casabonne, M.C.; Peralta, Patricia Angelica (Sociedad Argentina de Genética, 2025)
Poster